Islandske fagsprogsresurser: redaktørernes hensigter og brugernes behov - Þorbergsdóttir, Ágùsta (LexicoNordica, 2018)
This article considers the relationship between the aim of Icelandic specialised language dictionaries on the one hand and the needs of their users on the other hand. The different user groups are examined, together with the contexts in which the dictionaries are used, and the needs of individual users and user groups. The main motivations for compiling Icelandic specialised language dictionaries are analysed, and the ways in which the needs of their users are met in the dictionaries is also examined. Furthermore, current knowledge about the situation concerning the needs and wishes of users is reviewed. Finally, there is a brief discussion about the importance of compiling Icelandic specialised language dictionaries with regard to ensuring quality.